Anxiety and depression in the preoperative period of cardiac surgery - Gomes, Eduardo Tavares; Bezerra, Simone Maria Muniz da Silva (Rev Rene, 2017)
Objective: to analyze the frequency of anxiety and depression in the preoperative period of cardiac surgery in the scientific literature. Methods: this is an integrative review, whose corpus of analysis consisted of 17 articles, in a search carried out on the platforms MEDLINE (Pubmed), SCOPUS, CUIDEN, and SciELO. Results: the highest prevalences were 41.5% for anxiety and 28.3% for depression. Most of the studies on anxiety were developed from 2011; nine cohorts evaluated the negative repercussion of preoperative pain anxiety, postoperative anxiety, postoperative morbidity and mortality in the follow-up of up to 7.6 years. Conclusion: most studies reported anxiety and depression as significant conditions in the preoperative period.